Joost J. Oppenheim: 1934–2022. Issue 2 (23rd June 2022) - Wahl, Sharon M.; Young, Howard A.
ABSTRACT: Joost J. Oppenheim was born in 1934 in Venlo, Netherlands and died at the age of 87 on May 14, 2022. Not one to retire or rest on his laurels, Joe remained a Senior Investigator and Head of the Cellular Immunology Section in the Cancer Innovation Laboratory of the National Cancer Institute until his passing. In the years between 1934 and 2022, Joe lived a life filled with peril, poverty, persistence, brilliance, discovery, recognition, family and satisfaction. With Joe's passing comes the end of an era and the loss of a Father of Cytokine Research who was an amazing investigator, colleague, mentor and friend. Graphical Abstract: ‐